2018
DOI: 10.1007/s10107-018-1285-1
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic optimization with orthogonality constraint: explicit Łojasiewicz exponent and linear convergence of retraction-based line-search and stochastic variance-reduced gradient methods

Abstract: A fundamental class of matrix optimization problems that arise in many areas of science and engineering is that of quadratic optimization with orthogonality constraints. Such problems can be solved using line-search methods on the Stiefel manifold, which are known to converge globally under mild conditions. To determine the convergence rate of these methods, we give an explicit estimate of the exponent in a Lojasiewicz inequality for the (non-convex) set of critical points of the aforementioned class of proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 48 publications
(52 reference statements)
3
72
0
1
Order By: Relevance
“…The first algorithm even admits a global convergence rate of O(1/ǫ), in the same order as the gradient descent algorithm, which is faster than the subgradient method. In addition, we demonstrate that the first algorithm also admits a local linear convergence rate, by a delicate analysis on the Kurdyka-Lojasiewicz (KL) [6,11,34,20] property for problem (M). We illustrate in our numerical experiments the efficiency of the proposed algorithms when compared with the state-of-the-art methods for GTRS in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The first algorithm even admits a global convergence rate of O(1/ǫ), in the same order as the gradient descent algorithm, which is faster than the subgradient method. In addition, we demonstrate that the first algorithm also admits a local linear convergence rate, by a delicate analysis on the Kurdyka-Lojasiewicz (KL) [6,11,34,20] property for problem (M). We illustrate in our numerical experiments the efficiency of the proposed algorithms when compared with the state-of-the-art methods for GTRS in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The basic idea of the line-search method for the optimization problem is to search the optimal solution in the tangent space of the Stiefel manifold. We observed that line-search method based on the polar decomposition-based retraction updates the representation of a vertex through linear summation of other representations in iterations [25]. In our problem, that means:…”
Section: Approximated Algorithm In Graph Streamsmentioning
confidence: 88%
“…The problem with such format has been widely studied and concluded with no closed-form solution. State-of-the-art solution is to learn the solution through Riemann gradient approach [24] or line-search method on the Stiefel manifold [25], whose convergence analysis has attracted extensive research attention very recently. However, they are not suitable for streaming setting, becaus waiting for convergence brings in time uncertainty and gradient-based methods possess unsatisfied time complexity.…”
Section: Dynamic Graph Representation Learningmentioning
confidence: 99%
“…Alongside deterministic algorithms, the stochastic gradient descent method (SGD) and the stochastic variance reduced gradient method (SVRG) have also been extended to optimization over Riemannian manifold; see e.g. [28,30,38,61,62]. Compared to all these approaches, our proposed methods allow a nonsmooth objective, a constraint x i ∈ X i , as well as the coupling affine constraints.…”
Section: Related Literaturementioning
confidence: 99%
“…Combining (82), (83), (84) and (38), we obtain E[Ψ S (x k+1 1 , · · · , x k+1 N −1 , x k+1 N , λ k+1 , x k N )] − E[Ψ S (x k 1 , · · · , x k N −1 , x k N , λ k , x k−1 N )] (85)…”
Section: A4 Proof Of Lemma 312mentioning
confidence: 99%